Lepidobatrachus asper Budgett,1899 (Amphibia: Anura: Ceratophryidae): New country record, distribution map and natural history notes - Sugai, José Luiz Massao Moreira; Faggioni, Gabriel Paganini; Piatti, Liliana; Lemos, Anderson Aparecido; Souza, Franco Leandro; Prado, Cynthia Peralta de Almeida [UNESP] (My University, 2013)
Lepidobatrachus asper is a large to medium frog known from the Chaco lowlands of Paraguay and Argentina. We provide the first species record for the Brazilian Chaco, which extends the species geographical distribution ca. 73 km northeast from Puerto Casado, Alto Paraguay Departament, Paraguay. We also provide a distribution map and information about the species habitat conditions and diet. The Brazilian Chaco is still poorly surveyed, and the rapid environmental degradation can lead to local extinctions of certain species. © 2013 Check List and Authors.